TANGGUNG JAWAB MORAL: URAT NADI BISNIS YANG SEHAT - Andre Ata Ujan (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2014)
Business is a social entity which inevitably effects the quality of human life. Its success in supporting human life in general and, particularly, the long-term economic prospects it aims to achieve, require the real commitment of its agents to take moral values seriously in doing business. Instead of moral minimalism, a good and healthy business necessitates every businessman/woman to act beyond economic and legal interests to embrace “the genius of AND” as the ideal approach in doing business. Real commitment on seriously taking into account moral considerations in the process of business decision-making would in turn, in the long term, bring greater economic opportunities and, hence, enhance the prospect of business. At the centre of a good and healthy business is its agents’ commitment on taking all stakeholders’ interests to be their own. Doing justice to all stakeholders and to the public at large is, therefore, the life-blood of good and healthy businesses. A moral culture in business requires moral models to flourish and be shared commonly among all business agents. Kata-kata kunci: Tanggung jawab ekonomi; tanggung jawab hukum; tanggung jawab moral; intangible values; stakeholders; model moral.